Ulama Dayah and the Construction of Tolerance and Pluralism in Acehnese Society - Syarifuddin Syarifuddin (Sinthop)
This article explores the pivotal role of ulama dayah—traditional Islamic scholars—in shaping the discourse and practice of tolerance and pluralism in Aceh, Indonesia. Employing a qualitative approach that integrates literature review, document analysis, and semi-structured interviews with prominent ulama dayah and members of the Aceh Ulema Consultative Assembly (MPU), the study examines how these scholars conceptualize and enact tolerance in a society marked by both strong Islamic identity and growing diversity. The findings reveal that ulama dayah interpret tolerance as an Islamic principle grounded in the Shafi‘i tradition, emphasizing respect for difference while maintaining doctrinal boundaries. Their strategies in managing intra-Muslim diversity and interfaith relations include persuasive guidance, conflict mediation, educational outreach, and institutional collaboration through the MPU. The influence of ulama dayah extends beyond ritual matters to shaping communal norms and public policy, making them key agents in sustaining social cohesion. The study concludes that the Acehnese experience demonstrates the importance of culturally embedded religious authority in negotiating pluralism, and highlights the ongoing challenges and opportunities for adaptive leadership in an increasingly complex society.